2018
DOI: 10.1128/jvi.00731-18
|View full text |Cite
|
Sign up to set email alerts
|

Semen Exosomes Promote Transcriptional Silencing of HIV-1 by Disrupting NF-κB/Sp1/Tat Circuitry

Abstract: Exosomes play various roles in host responses to cancer and infective agents, and semen exosomes (SE) inhibit HIV-1 infection and transmission, although the mechanism(s) by which this occurs is unclear. Here, we show that SE block HIV-1 proviral transcription at multiple transcriptional check points including transcription factor recruitment to the LTR, and transcription initiation and elongation. Biochemical and functional studies show that SE inhibit HIV-1 long terminal repeat (HIV-LTR)-driven viral gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 64 publications
1
69
0
1
Order By: Relevance
“…We conclude from these data that exposure of lymphocytes to the level of SE used in this study (100 µg·mL −1 ) does not alter basal or stimuli‐induced cell death. These results are consistent with observations in cell lines .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…We conclude from these data that exposure of lymphocytes to the level of SE used in this study (100 µg·mL −1 ) does not alter basal or stimuli‐induced cell death. These results are consistent with observations in cell lines .…”
Section: Resultssupporting
confidence: 93%
“…Prior studies have shown that SE do not alter basal activity of the HIV promoter but the effect of SE on activation of cellular programs is unknown. To evaluate the effect of SE on viral and cellular activation, we examined the response of primary PBMCs isolated from the whole blood of 11 HIV‐infected individuals that were receiving suppressive ART (PBMC ART ) and had suppressed viral loads (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…These studies will determine if SE induce viral reactivation in lymphocytes isolated from HIV-infected ART-suppressed individuals. Of note, SE had no effect on viral reactivation in an in vitro cell model of HIV-1 latency [139].…”
Section: Semen Exosome Immunomodulatory Functionsmentioning
confidence: 87%
“…Although the exact mechanism(s) by which SE inhibit HIV-1 infection is unknown, studies show that multiple steps in the HIV-1 lifecycle are affected by SE including: (1) conversion of ssRNA to dsDNA (reverse transcription), (2) copying of integrated proviral DNA, and (3) transcription of viral RNA from proviral DNA [63,139], as depicted in Figure 5. Since three of these replication steps are key points where HIV-1 mutations arise, SE may inhibit infection through multiple mechanisms [137].…”
Section: Semen Exosomes Inhibit Hiv-1 Infectionmentioning
confidence: 99%
See 1 more Smart Citation